The Monroe Doctrine: Republicans’ Perspective in the Formation Years of the Versailles-Washington System - S. O. Buranok (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Monroe Doctrine occupies a unique place in the US history. It became one of the key foreign policy documents of its time and provided the basis for a wide variety of interpretations of the United States’ role and goals in the international arena at turning points of world history. One of these moments was the turn of the 1910s−1920s, when a new Versailles-Washington order of international relations was emerging. In the US public discourse, this period was marked by intense debates between supporters of the Democratic President V. Wilson and his isolationist opponents. Both Republicans and Democrats constantly referred to the Monroe Doctrine, on the one hand, to justify their own views on US foreign policy in the new conditions, and, on the other hand, to refute the arguments of their political opponents. The controversy surrounding the Monroe Doctrine has been reflected in publications in periodicals and analytical journals, as well as in cartoons. Studying these materials, it is possible to trace the evolution of the approaches of American politicians, experts, editors, and journalists to the Monroe Doctrine. The arguments of the Republicans against the ‘internationalist’ interpretation of the Monroe Doctrine that emerged in the face of the changing global context after the First World War are of particular interest. The study shows that at the initial stage of discussions (1920), the Monroe Doctrine was used by the Republicans primarily to criticize W. Wilson’s concept of international relations in general and his position on the League of Nations in particular. At the next stage (1921−1923), the debate focused around the need to revise the Monroe Doctrine itself, that aroused due to new trends in the development of international relations in the Far East and, in particular, because of the increasing competition between the United States and Japan. The author identifies several main approaches to the interpretation of the Monroe Doctrine formulated during the public debate in 1921−1923. It is shown that, despite significant divergences of view, both isolationists and internationalists eventually came to broader interpretations of the Monroe Doctrine, recognizing the need to extend its principles to the entire Asia-Pacific region.